Genome-wide identification of Argonautes in Solanaceae with emphasis on potato - Zhen Liao (Nature Portfolio, 2020)
Abstract Regulatory small RNAs (sRNAs) play important roles in many fundamental processes in plant biology such as development, fertilization and stress responses. The AGO protein family has here a central importance in gene regulation based on their capacity to associate with sRNAs followed by mRNA targeting in a sequence-complementary manner. The present study explored Argonautes (AGOs) in the Solanaceae family, with emphasis on potato, Solanum tuberosum (St). A genome-wide monitoring was performed to provide a deeper insight into gene families, genomic localization, gene structure and expression profile against the potato late blight pathogen Phytophthora infestans. Among 15 species in the Solanaceae family we found a variation from ten AGOs in Nicotiana obtusifolia to 17 in N. tabacum. Comprehensive analyses of AGO phylogeny revealed duplication of AGO1, AGO10 and AGO4 paralogs during early radiation of Solanaceae. Fourteen AGOs were identified in potato. Orthologs of AGO8 and AGO9 were missing in the potato genome. However, AGO15 earlier annotated in tomato was identified. StAGO15 differs from the other paralogs having residues of different physico-chemical properties at functionally important amino acid positions. Upon pathogen challenge StAGO15 was significantly activated and hence may play a prominent role in sRNA-based regulation of potato defense.